The risk factors associated with the prevalence of pain and self-reported physician-diagnosed osteoarthritis in Great Britain’s Olympians - Cooper, Dale (2016)
Background: Affecting approximately one in four adults over the age of 50 years in the UK, knee pain is a leading cause of disability in the elderly and bears a significant economic cost. Despite the plethora of studies that have investigated the factors associated with the onset of knee pain and osteoarthritis (OA) in the sedentary population, relatively little is known about the prevalence and factors associated with musculoskeletal pain and OA in an athletic sporting population.